Association between oral mucositis and xerostomia during breast cancer chemotherapy treatment - Marinho, Pabliane Matias Lordelo (2023)
Introduction: Chemotherapy can cause adverse events in the oral cavity, such as mucosal lesions and changes in salivary flow. However, the association between these events has not been evaluated. Objective: To evaluate the association between oral mucositis and xerostomia during chemotherapy for the treatment of breast cancer. Methods: This was an observational and prospective study carried out with 140 women who underwent chemotherapy treatment for breast cancer in three cancer centers, evaluating them in two segments: in the intermediate cycle and at the end of treatment. Results: A high frequency of oral mucositis (87.5%) and xerostomia (82.9%) was observed after exposure to chemotherapy agents, but there was no significant association between both in the study segments (p >0.05 ). However, 60% simultaneously manifested oral mucositis and xerostomia in at least one segment, with a significant association of the double-hit being observed between the studied segments (p <0.001). Conclusion: Oral mucositis and xerostomia were not consistently associated in breast cancer patients during chemotherapy.